2000
DOI: 10.1021/ac991186r
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Description of Microdialysis with Mass Transport Coupled to Chemical Events

Abstract: A random-walk simulation of microdialysis is used to examine how a reaction that consumes analyte in the medium external to the probe affects the extraction and recovery processes. The simulations suggest that such a reaction can promote the extraction process while simultaneously inhibiting the recovery process, which appears to be consistent with recent experimental evidence of asymmetry in the extraction and recovery of the neurotransmitter, dopamine, during brain microdialysis. This suggests that quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 23 publications
4
54
0
Order By: Relevance
“…These concentrations are consistent with those in the literature when accounting for differences in in vitro recovery of the dialysis probes [3,[23][24][25]. (Although in vitro recovery is not always an accurate reflection of in vivo recovery [26], this correction facilitates comparison to literature values.) Basal concentrations of taurine, glutamine and serine are not listed because the peaks for these analytes were typically off-scale when the detector settings were optimized for sensitivity; however, use of automatic gain control or data acquisition boards with greater dynamic range will allow these compounds to quantified from the same electropherograms as the lower level compounds.…”
Section: Selectivitysupporting
confidence: 84%
“…These concentrations are consistent with those in the literature when accounting for differences in in vitro recovery of the dialysis probes [3,[23][24][25]. (Although in vitro recovery is not always an accurate reflection of in vivo recovery [26], this correction facilitates comparison to literature values.) Basal concentrations of taurine, glutamine and serine are not listed because the peaks for these analytes were typically off-scale when the detector settings were optimized for sensitivity; however, use of automatic gain control or data acquisition boards with greater dynamic range will allow these compounds to quantified from the same electropherograms as the lower level compounds.…”
Section: Selectivitysupporting
confidence: 84%
“…In contrast, microdialysis results report increases of Ϸ8-fold, which would correspond to 40 nM extracellular dopamine (3), a value more than an order of magnitude less than the current estimate. Although disturbances of the tissue with either probe (44)(45)(46) or errors in calibration may account for this large difference, differences in sampling region are also a likely factor. The carbon-fiber electrode is Ϸ40-fold shorter and 50-fold smaller in diameter than typical microdialysis probes.…”
Section: Discussionmentioning
confidence: 99%
“…A 5.5-fold increase in PEA for a microdialysis probe versus a 90 m capillary sampling method was noted. A random walk simulation demonstrated that microdialysis perturbs metabolic processes (Yang et al, 2000a). Amperometric probes are not free from perturbation due to consumption of the analyte; however, the difference in flux consumption is ca.…”
Section: Physiological Host Responsementioning
confidence: 99%